Environmental Hydraulics Research - Ramos, Helena M.; Carravetta, Armando; McNabola, Aonghus; Adeyeye, Kemi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book aims to provide research and engineering applications related to water and hydraulic problems. It is comprised of scientific papers in all topics of hydraulics, in particular, on sustainable water management, environmental hydraulics, ecohydraulics, water-energy nexus, and systems protection and efficiency. Safety and innovation issues, interdisciplinary problems, and linkage of theory to experimental and field applications can also be found within. Solutions of water problems in the form of prediction models, flow simulations, engineering systems, monitoring, management strategies covering scientific investigations and/or experimental or field studies of flow behaviour, hydrodynamics, and climate changes effects and adaptation, new design solutions, innovative approaches in the field of environment, hydraulics, techniques, methods, and analyses to address the new challenges in environmental hydraulics are alo presented and explored. This topic is studied both from a technical and environmental point of view, with the objective of protecting and enhancing the quality of the environment. In a cross-disciplinary field of study, this book comprises open channel/river flows and pressurised systems, combining, among others, new technological, social, and environmental hydraulic challenges, working in water-related fields with available information, new concepts and tools, new design solutions, eco-friendly technologies, and the advanced materials necessary to address the increasing challenges of ensuring a sustainable water environment by promoting the adaptation, flexibility, integration, and sustainability of recognised environmental solutions.